Religious Moderation in the Frame of Tolerance in Lau Pengulu Village, Mardinding District, Karo Regency, North Sumatra - Mhd. Yadi Harahap; Desi Indriani Rahma Wati; Abdillah Habib Saputra Sinaga; Nurwanda Safitri Br Tompul; Sabrina Maharani Putri (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This research investigates the role of religious moderation in promoting religious tolerance in Lau Pengulu Village, North Sumatra. This village is a microcosm of the complexity of religious harmony in Indonesia. In the context of significant religious diversity, the question of how to be religious in moderation and maintain tolerance becomes relevant. This research sample used a purposive withdrawal method and interviews with 30 participants from various religious backgrounds. The results show that the practice of religious moderation supports tolerance between religious groups. This practice is manifested in joint participation in religious activities and social cooperation. These findings have practical significance for the development of educational programs, policies, and the promotion of interfaith cooperation.